Longitudinal evaluation of innate immune responses to three doses of CoronaVac vaccine - Cao, Cheng; Jiang, Junfeng; Liu, Min; Dai, Yaping; Chang, Tianzhi; Ji, Tuo; Gong, Fang (Frontiers in Immunology, 2023)
The adaptive immune responses induced by inactivated COVID-19 vaccine has been extensively studied. However, few studies have analyzed the impact of COVID-19 vaccination on innate immune cells. Here in this study, we recruited 62 healthcare workers who received three doses of CoronaVac vaccine and longitudinally profiled the alterations of peripheral monocytes and NK cells during vaccination. The results showed that both the monocyte and NK cell subsets distribution were altered, although the frequencies of the total monocyte and NK cells remained stable during the vaccination. Additionally, we found that both the 2 nd and 3 rd dose of CoronaVac vaccination elicited robust IFN-γ-producing NK cell response. Our data provided necessary insights on innate immune responses in the context of three homologous CoronaVac dose vaccination, and supplied immunological basis for the future design of inactivated vaccines against SARS-CoV-2 or other viruses.